2010
DOI: 10.3109/08860220903491190
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Decreased Renal Function in Taxi Drivers in Tehran, Iran

Abstract: Background and objectives. The rapid increase in end stage renal disease (ESRD) prevalence, plus the enormous cost of treatment, necessitates an urgent approach to implement strategies to prevent development and progression of ESRD, especially in the developing world. Screening that leads to early identification and treatment has been recommended, as it may slow or prevent progression to a more expensive and disabling stage of the disease and thus may save lives as well as finite resources. Methods. In 2007, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 35 publications
3
19
2
Order By: Relevance
“…The reported prevalence rates for diabetes and hypertension in other areas of Iran varies considerably. Among studies on CKD in Iran, the reported prevalence in three studies was 9.2%, 13.7%, and 29.0% for diabetes and 9.9%, 25.8%, and 17.4% for hypertension [10], [26], [27]. However, in a recent national surveillance on approximately 30,000 Iranians aged 15–64 years, prevalence of diabetes and hypertension was reported as 17.4% and 3.5%, respectively [31].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The reported prevalence rates for diabetes and hypertension in other areas of Iran varies considerably. Among studies on CKD in Iran, the reported prevalence in three studies was 9.2%, 13.7%, and 29.0% for diabetes and 9.9%, 25.8%, and 17.4% for hypertension [10], [26], [27]. However, in a recent national surveillance on approximately 30,000 Iranians aged 15–64 years, prevalence of diabetes and hypertension was reported as 17.4% and 3.5%, respectively [31].…”
Section: Discussionmentioning
confidence: 97%
“…A part of the studies, even within a country, have reported very different rates [24]. For example, prevalence of CKD–S3-5 was reported as 18.7% in Japanese general population [25] and as 18.9%, 7.8%, and 6.5% in 3 other studies from Iran [10], [26], [27]. This can be related to true differences in prevalence of the disease in different populations, variation in the methodology that was used, and differences in demographic characteristics of study participants, including age structure.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study involving more than 30,000 subjects, it was shown that more significant underestimation occurred when using the corrected Cockcroft-Gault equation compared to the MDRD formula in subjects older than 55 years, although a strong correlation was observed between the 2 methods (r = 0.91, P = 0.001) [8]. In our study, although the CKD stage weakly contributed to a higher HBsAb titer, it did not significantly correlate with the seroconversion rate.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have reported that long-term hypertension, diabetes, hyperuricemia, renal arteriosclerosis, ischemic heart disease, and smoking can cause CKD [18][19][20][21][22][23]. In the present patient, multiple chronic diseases and a long-term smoking habit led to the occurrence of CKD.…”
Section: Discussionmentioning
confidence: 57%